A Rare Case of Juvenile Xanthogranuloma in 8 Months Old Baby with Dyslipidemia - Jessica Herlianez Saiful; Rina Gustia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Juvenile xanthogranuloma (JXG) is a non-Langerhans cell histiocytosis disease of childhood. But due to rarity of non Langerhans cell hystiosis itself, the exact prevalence of juvenile xanthogranuloma remain unknown with only a few epidemiological journal ever published. Juvenile xanthogranuloma usually wihout lipid abnormality and systemic involvement. But association between JXG and lipid abnormalities is still not well understood. We describe a patient with multiple cutaneous JXG who also developed hyperlipidemia. Case: A case of a 8 months-old baby patient with juvenile xanthogranuloma is reported. Patient parents noticed yellowish dots on child’s face since six months ago, and it was gradually increase in size and number, and spread to trunks, upper and lower limb since 2 months ago. Patients got formula milk since 7 months ago. Patients father has uncontrolled hypercholesterolemia, and grandparents had controlled dyslipidemia. Dermatological state showed yellowish plaque and papule on the face, trunk, lower limb, and upper limb. Dermoscopy show yellowish papule with sun setting appearance and branched and linear vessel on orange yellow background. Laboratory finding showed elevated lipid serum. Foam cell and Touton giant cell is found on histopathology examination. Discussion: The presented case demonstrates that skin lesions in patients with diagnosed JXG may have a variable clinical presentation, ranging from single to diffuse skin lesions, also present from the birth to childhood. The diagnosis requires histopathological confirmation to avoid misdiagnosis of malignant disease. Association between JXG and lipid abnormalities remain unknown, with most of the patient show normal lipid serum. Majority of patients presenting lesions limited to the skin requires only a strict dermatological observation.